Wishes as bene- and malefactive speech acts. On the basis of discrediting parliamentary speeches in the Polish Lower House - Jurewicz, Magdalena (Scripta Neophilologica Posnaniensia, 2019)
What will be analysed in the paper, from the pragmalinguistic perspective, is the specificity and the positioning of wishes in an MP’s speech as a particular type of text. In my research, I would like to shed some light on the multifunctioning of such speech acts in the public performances, to which parliamentary speeches belong, which stems from the multitude of their addressees. I will be particularly interested in the change of the illocutionary force of wishes which, thanks to the influence of the irony that they contain, may serve the opposition politicians to mock the ruling party’s MPs. This, in turn, can indirectly lead to the disparagement of the latter. In a broader sense it can also be the result of a general persuasive function of all political speeches. The marking of irony is very specific for a given culture or even the idiolect of particular MPs. The precise knowledge of the possible indirect readings of some MPs’ utterances, and the techniques for deciphering ironic expressions would be very valuable for interpreters who have just recently begun their work in e.g. the European Parliament, where the speeches of MPs are interpreted simultaneously.